2019
DOI: 10.1200/jco.2019.37.15_suppl.3003
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 study evaluating the safety, tolerability, pharmacokinetics (PK), and efficacy of AMG 510, a novel small molecule KRASG12C inhibitor, in advanced solid tumors.

Abstract: 3003 Background: The KRASG12C mutation is found in approximately 13% of lung adenocarcinomas and 1–3% of other solid tumors, but there is no approved therapy that targets this mutation. AMG 510 is a novel small molecule that specifically and irreversibly inhibits KRASG12C by locking it in an inactive GDP-bound state. Methods: This phase 1, first-in-human, open-label, multicenter study (NCT03600883) is evaluating the safety, tolerability, PK, and efficacy of AMG 510 in adult patients (pts) with locally-advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
138
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(141 citation statements)
references
References 0 publications
3
138
0
Order By: Relevance
“…This discovery spurred the race to develop KRAS-G12C-targeting drugs for clinical use. AMG510 and MRTX1257 were the first ones to be developed as drugs to target KRAS G12C mutant for non-small cell lung cancer [274,[276][277][278]. The results from phase I trials were promising and showed a 50% response rate for patients with KRAS G12C mutations.…”
Section: Is Ras Druggable?mentioning
confidence: 99%
“…This discovery spurred the race to develop KRAS-G12C-targeting drugs for clinical use. AMG510 and MRTX1257 were the first ones to be developed as drugs to target KRAS G12C mutant for non-small cell lung cancer [274,[276][277][278]. The results from phase I trials were promising and showed a 50% response rate for patients with KRAS G12C mutations.…”
Section: Is Ras Druggable?mentioning
confidence: 99%
“…All patients had received at least two lines of prior systemic therapy. AMG 510 achieved a 50% response rate in patients with KRASG12C-positive NSCLC, according to results from a phase I study presented by Fakih et al [9].…”
Section: Kras-is There Light On the Horizon For A Hard-totarget Altermentioning
confidence: 81%
“…Therefore, limiting the sequence space 61 to sequences energetically similar to or better than the wild-type sequence is reasonable. 62 A simplified workflow for fries/EWAK * is presented in Fig 1. Compared to the 63 previous state-of-the-art algorithm BBK * , fries and EWAK * improve runtimes by up 64 to 2 orders of magnitude, fries decreases the size of the sequence space by up to more 65 than 2 orders of magnitude, and EWAK * decreases the number of conformations 66 included in partition function calculations by up to almost 2 orders of magnitude. design algorithms approximate these partition functions for each state using either 104 stochastic [50][51][52][53] or provable [2, 12, 29-31, 33, 53] methods.…”
mentioning
confidence: 93%